2020
DOI: 10.1186/s12983-020-00367-9
|View full text |Cite
|
Sign up to set email alerts
|

Female northern grass lizards judge mates by body shape to reinforce local adaptation

Abstract: Background: Identifying the factors that contribute to divergence among populations in mate preferences is important for understanding of the manner in which premating reproductive isolation might arise and how this isolation may in turn contribute to the evolutionary process of population divergence. Here, we offered female northern grass lizards (Takydromus septentrionalis) a choice of males between their own population and another four populations to test whether the preferences that females display in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Takydromus septentrionalis is not among lizard species displaying evident male–male agonistic behavior ( Ji et al 1994 ; Du and Yao 2007 ; Guo et al 2020 ). Evidence from field observations reveals that northern grass lizards are active in relatively stable home ranges, of which the mean size is greater in males than in females of the same SVL and greater in larger individuals than in smaller ones of the same sex, and that males increase mating opportunities primarily by increasing their home range (and thus the number of females encountered) rather than male–male competition ( Ji et al 1994 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takydromus septentrionalis is not among lizard species displaying evident male–male agonistic behavior ( Ji et al 1994 ; Du and Yao 2007 ; Guo et al 2020 ). Evidence from field observations reveals that northern grass lizards are active in relatively stable home ranges, of which the mean size is greater in males than in females of the same SVL and greater in larger individuals than in smaller ones of the same sex, and that males increase mating opportunities primarily by increasing their home range (and thus the number of females encountered) rather than male–male competition ( Ji et al 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…We collected 253 lizards (122 males and 131 females) larger than 50 mm snout–vent length (SVL) in early April 2017 from a previous studied population ( Ji et al 2007 ; Cai et al 2012 ; Guo et al 2020 ) in Lishui (28°46ʹN, 119°92ʹE), East China. Lizards were transported to our laboratory in Hangzhou, where they were weighed, measured (for SVL and tail length), and numbered via unique combinations of clipped toes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female T. septentrionalis can lay up to 9 clutches with 1-5 eggs each per breeding season from April to August (Ji et al, 2007;Luo et al, 2010); female T. sexlineatus can lay up to 5 clutches with 1-4 eggs each per breeding season also from April to August (Xu & Ji, 2000;Zhang & Ji, 2004). Evidence from T. septentrionalis has shown that males are the less choosy sex and can mate at extreme phylogenetic distances, either with conspecific females from distant populations, or even with heterospecific but congeneric females (Guo et al, 2020).…”
Section: Study Speciesmentioning
confidence: 99%